(untitled) (The Pakistan Development Review, 1992)
This paper examines empirical determinants of the Pakistani rupee exchange rate since the advent of the managed float in 1982. The behaviour of the nominal exchange rate results from policy intervention carried out by the monetary authorities. Various testable hypotheses are developed in order to discern the factor(s) which can be the determinants of the nominal rupee exchange rate. In the shon run, authorities follow a contingent policy rule with respect to movements of the U. S. dollar against the SDR. Based on vector autoregression techniques, the error correction model is employed to check the consistency of the shon-run adjusunent process, given the authorities’ longrun target rupee value. The ’revealed’ policy is to panly offset the inflation differential between Pakistan and its major trading parUlers. Under plausible conditions, the burden of adjusunent and recessionary conditions are likely to occur in the Pakistani expon sector.